Terapi Kipas untuk Meredakan Sesak Napas - Rica Fitria; Riri Maria; Agung Waluyo; Dasna Dasna; Eliana Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to provide evidence-based information to support nursing care with clinical expertise in relieving dyspnea. The method used is a literature review on the Pubmed, EBSCO Host, Google Scholar and ClinicalKey databases with predetermined keywords. The results showed that the fan therapy intervention had a beneficial effect in relieving dyspnea experienced by terminal cancer patients. In conclusion, fan therapy intervention proved to be effective in reducing dyspnea. Keywords: Dyspnea, Fan-on-Face Therapy, Terminal Cancer